Effect of metabolic syndrome or type II diabetes mellitus on the occurrence of recurrent vascular events in hypertensive patients - Vlek, A L M; van der Graaf, Y; Spiering, W; Visseren, F L J (Journal of human hypertension, 2008)
Patients with hypertension and manifest vascular disease are at high risk for recurrent cardiovascular diseases. It is unknown if the metabolic syndrome further increases the risk in these patients. This study aims to quantify the effect of metabolic syndrome and type II diabetes on cardiovascular events in hypertensive patients with vascular disease. A total of 2196 hypertensive patients with vascular disease (cerebrovascular disease (34%), coronary heart disease (50%), peripheral arterial disease (28%), abdominal aortic aneurysm (13%)) from the Second Manifestations of Arterial Disease study were followed for up to 10 years (mean 3.9 years) for death, stroke and myocardial infarction. Age and sex adjusted hazard ratios (HR) were calculated for hypertensive patients with metabolic syndrome but without diabetes ( n =775) and for hypertensive patients with type II diabetes ( n =381), compared to merely hypertensive patients ( n =1040). Forty-nine percent had metabolic syndrome (NCEP ATPIII definition) and 17% had type II diabetes. Metabolic syndrome predicted vascular death (HR 1.41, 95% confidence interval (CI) 1.01–1.98), stroke (HR 1.36, 95% CI 0.85–2.16) and myocardial infarction (HR 1.40, 95% CI 0.97–2.01). Type II diabetes accounted for even higher risks of vascular end points (HR 1.41–1.64). The effect of metabolic syndrome on future events could not be explained by the presence of type II diabetes. Even in high-risk patients with hypertension and vascular disease, presence of metabolic syndrome or type II diabetes identifies patients at high risk for future cardiovascular events. Identifying metabolic syndrome patients may direct therapy focusing on treatment of insulin resistance by reducing weight and increasing physical activity.